Performance environment and nested task constraints influence long jump approach run: a preliminary study - Panteli, F.; Smirniotou, A.; Theodorou, A. (Journal of Sports Sciences, 2016)
The purpose of the study was to investigate possible changes at step pattern and technical performance of the long jump approach run in seven young long jumpers by modifying the performance environment (long jump runway versus track lane) and the nested actions (run-through with take-off versus complete long jump). Our findings suggest that the step pattern and technical aspects of the approach run are affected by environmental context and nested task constraints. In terms of environmental context, it appears that practising the training routine of run-through followed by take-off on the long jump runway allows athletes to simulate competition conditions in terms of step regulation and technical efficacy. The task of run-through followed by take-off on the track lane failed to initiate visual perception, step regulation and technical efficiency at the steps preceding the instant of take-off. In terms of nested task constraints, when run-ups were followed by jump for distance instead of only a take-off, a higher level of consistency was achieved and step regulation was based on perception-action coupling. Practising long jump run-up accuracy at a setting not containing the informational elements of the performance environment fails to develop the key elements of the skill.